2004
DOI: 10.1007/s00167-003-0423-2
|View full text |Cite
|
Sign up to set email alerts
|

Isolated complete popliteal artery rupture associated with knee dislocation

Abstract: Complete dislocation of the knee is a rare injury, and is frequently associated with injuries to other structures in the popliteal fossa. Prompt recognition of associated popliteal artery disruption and early revascularization is paramount for successful and functional results. The necessity for emergency vascular reconstruction markedly complicates an already difficult orthopaedic problem. Arteriography is recommended in all cases of complete dislocation of the knee.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 6 publications
0
16
0
3
Order By: Relevance
“…With participation in youth sports near record numbers, the identification, diagnosis, and treatment of pediatric ACL injuries have increased nearly 10-fold. 56 Despite the increasing incidence of ACL injuries, multiligament knee injuries in the adolescent population are scarce, 13 , 26 , 59 and thus the literature on indications, surgical timing, outcomes, and complications is limited. 40 …”
mentioning
confidence: 99%
“…With participation in youth sports near record numbers, the identification, diagnosis, and treatment of pediatric ACL injuries have increased nearly 10-fold. 56 Despite the increasing incidence of ACL injuries, multiligament knee injuries in the adolescent population are scarce, 13 , 26 , 59 and thus the literature on indications, surgical timing, outcomes, and complications is limited. 40 …”
mentioning
confidence: 99%
“…This helps in the diagnosis of patients who develop occlusive lesions on a delayed basis. 6,9,18 Ankle-brachial Index Some authors advocate use of the ABI in addition to physical examination to determine the need for arteriography. 9,19 Mills et al 19 reported 100% sensitivity, specificity, and positive predictive value for significant arterial injury when patients had an ABI <0.9.…”
mentioning
confidence: 99%
“…The mechanism of popliteal artery trauma is similar to that of knee dislocation. [5][6][7]11,12 The femoral condyle usually follows the posterior split of the medial tibial plateau producing a posterior subluxation of the knee joint in fl exion. As this subtle dislocation can be reduced in extension and the displacement of the fracture usually is minimal, the vascular compromise can be misdiagnosed, especially when inexperienced doctors perform the initial consultation.…”
Section: Discussionmentioning
confidence: 99%